Gestão de resíduos sólidos - Barra dos Coqueiros - Rocha, Viviane Gomes (2007)
The garbage produced by diverse human beings activities is one of the biggest problems faced in the present time, generating serious politic, social, economic, technical, environmental and health conflicts. The bigger the number of people who live in the city, the greater the generation of residues will be. The result is the increasing deterioration of environmental conditions with the visible increase of pollution levels. The general objective of this research is to diagnose the current situation of solid residues in the city of Barra dos Coqueiros, subsidizing the municipal government for the elaboration of a Plan of Integrated Management of Solid Residues. The information used for this work was obtained through specialized bibliography and legislative documents, questionnaires applied to the family heads, municipal government, communitarian leaderships and local authorities, sector of health, diagnosis and characterization of solid residues. The city of Barra dos Coqueiros is in the east of the state of Sergipe. In the east, it meets the Atlantic Ocean and in the west it meets the Pomonga and Sergipe rivers. According to data of IBGE, 2000, it has about 17.807 inhabitants and 4,448 domiciles, and among these, 113 have been used as a sample, aiming at analyzing the current systematics of the solid residues in the city. As a conclusion of this study it was verified that the city possesses daily system of collection, transport through garbage truck and final disposal. However, it was perceived that the current system adopted by the municipal government is inefficient mainly due to an incorrect final disposal system, which in a period of one year was placed in three distinct areas, the first one in a landfill in the city of Barra dos Coqueiros, the second in a landfill in the city of Santo Amaro das Brotas and the third in a landfill named ´Aterro Controlado da Terra Dura` in Aracaju. What is still necessary for the community is the pre-disposition for treating and also minimizing the generation of the residues in its source and also some environmental awareness of the damages that the residues cause to the way of life of the community. As future studies recommendations, a plan of integrated management of solid residues is suggested, the study of areas for the implantation of a sanitary landfill, the elaboration of Laws that deal with the solid residues and complement the existing Managing Plan with the subject in question, the incentive of projects of selective collection and recycling, as well as to guide and to divulge environmental politics, and mainly to stimulate programs of environmental education in all levels, acting together with the citizens in the formation of the environmental conscience.